Prevalence of primary and secondary infertility from tertiary center in eastern Saudi Arabia - Haifa A. Al-Turki (Middle East Fertility Society Journal, 2015)
Background and objective: Infertility is a universal problem with very limited data in Saudi Arabia. In this retrospective study, we analyzed patients attending the infertility clinics at King Fahd Hospital of the University in Alkhobar, Saudi Arabia, during 2012. Patients and methods: All patients who attended the infertility clinics between January and December 2012 were part of the study. The data were collected from the Quadramed Filing system and medical charts for age, length of marriage, primary or secondary infertility, laboratory and radiological investigations, and semen analysis of the husbands. The data were entered into a database and analyzed using SPSS version 14. Results: During the study period, 2414 patients were seen at all the clinics of obstetrics and gynecology department of the hospital. In the two infertility and reproductive medicine clinics, 457 patients were seen with primary and secondary infertility. The data from these 457 patients were analyzed. The overall prevalence of infertility was 18.93%. The average age was 33.38 ± 5.39 (20–52) years and the average length of marriage was 64.71 ± 50.84 (12–258) months. Three hundred sixty-one (78.99%) had primary infertility and 388 had no known diseases. The mean follicle-stimulating hormone (FSH) level was 5.91 ± 3.56 IU/L, mean leutinizing hormone level was 4.61 ± 2.11 IU/L and mean prolactin level was 18.4 ± 8.35 μg/L. The semen parameters showed that 127 (27.7%) subjects had a count less than 15 million, of which 87 (68.5%) were azoospermic. The average progressive motility was 36.62 ± 27.43%. Conclusions: Our study shows that the prevalence of infertility was 18.93% with the primary infertility more common than the secondary. We believe that infertility is an emerging issue and a cause for concern for Saudi Arabia and requires clear direction in the future before it becomes a major public health problem.